Amplitude dynamics of the charge density wave in LaTe3: theoretical description of pump-probe experiments - Dolgirev, Pavel; Rozhkov, A. V.; Zong, Alfred; Kogar, Anshul; Gedik, Nuh; Fine, Boris V. (Physical review, 2020)
We formulate a dynamical model to describe a photoinduced charge density wave (CDW) quench transition and apply it to recent multiprobe experiments on LaTe3 [A. Zong et al., Nat. Phys. 15, 27 (2019)]. Our approach relies on coupled time-dependent Ginzburg-Landau equations tracking two order parameters that represent the modulations of the electronic density and the ionic positions. We aim at describing the amplitude of the order parameters under the assumption that they are homogeneous in space. This description is supplemented by a three-temperature model, which treats separately the electronic temperature, temperature of the lattice phonons with stronger couplings to the electronic subsystem, and temperature of all other phonons. The broad scope of available data for LaTe3 and similar materials as well as the synergy between different time-resolved spectroscopies allow us to extract model parameters. The resulting calculations are in good agreement with ultrafast electron diffraction experiments, reproducing qualitative and quantitative features of the CDW amplitude evolution during the initial few picoseconds after photoexcitation.